(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article provides detailed information on the role of pharmaceutical technologies in microbiological laboratories. In particular, information about the role of microbiological laboratories in the pharmaceutical industry, microbiological tests and quality control, microbiology and biotechnology in pharmaceutical technologies, safety and quality assurance in microbiological laboratories is given.